Maya® 5 Fundamentals - Lewis, Garry (New Riders Publishing, 2011)
With the powerful 3D modeling program Maya 5, you're limited only by your own imagination. To set it free, look no further than this indispensable guide! In these pages, veteran animator Jim Lammers (who brought life to the Sony/Tristar film Starship Troopers) takes you from a review of 3D fundamentals to full-blown Maya 5 content creation. In the process you'll learn about Maya's interface and tools; modeling with NURBS and polygons; applying materials and textures; rendering stills and animations; using particle systems, dynamics, and paint effects; and more. By detailing not just how Maya works but the 3D principles and fundamentals that guide its use, this volume will have your creating brave new worlds of your own in no time. Also included is complete coverage of all of Maya 5's new features, including improved rendering options and never-before-seen atmospheric effects made possible by extensions to Maya Fluid Effects. A companion CD includes video-captured movies that walk you through every tutorial in the book.